Somatodendritic dopamine release: recent mechanistic insights - Rice, Margaret E. (Philos Trans R Soc Lond B Biol Sci, 2015)
Dopamine (DA) is a key transmitter in motor, reward and cogitative pathways, with DA dysfunction implicated in disorders including Parkinson's disease and addiction. Located in midbrain, DA neurons of the substantia nigra pars compacta project via the medial forebrain bundle to the dorsal striatum (caudate putamen), and DA neurons in the adjacent ventral tegmental area project to the ventral striatum (nucleus accumbens) and prefrontal cortex. In addition to classical vesicular release from axons, midbrain DA neurons exhibit DA release from their cell bodies and dendrites. Somatodendritic DA release leads to activation of D2 DA autoreceptors on DA neurons that inhibit their firing via G-protein-coupled inwardly rectifying K(+) channels. This helps determine patterns of DA signalling at distant axonal release sites. Somatodendritically released DA also acts via volume transmission to extrasynaptic receptors that modulate local transmitter release and neuronal activity in the midbrain. Thus, somatodendritic release is a pivotal intrinsic feature of DA neurons that must be well defined in order to fully understand the physiology and pathophysiology of DA pathways. Here, we review recent mechanistic aspects of somatodendritic DA release, with particular emphasis on the Ca(2+) dependence of release and the potential role of exocytotic proteins.